‘Trojan horse’ or ‘Workhorse’? the evolution of U.S.–Japanese joint ventures in the United States - Hennart, Jean‐François; Roehl, Thomas W.; Zietlow, Dixie S. (Strategic Management Journal, 1999)
Foreign investors and their domestic joint venture partners must find ways to share the benefits of the venture if both sides are to be satisfied. Some work in the literature on joint ventures has asserted that there is a danger in all joint ventures, and especially joint ventures with Japanese, that one side will exploit the venture for its own gain, using it as a Trojan Horse. To test this assertion, we build a full data set of Japanese firms with joint ventures in the United States and track the ventures over time. Our data show that the Japanese partners do not take actions consistent with the Trojan Horse hypothesis. Copyright © 1999 John Wiley & Sons, Ltd.